Information design and students' assimilation after Covid-19 - Andaleep Sadi Ades (Social Medicine Publication Group, 2022)
The learning strategies have changes after Covid-19. Online and self-learning method become the main axis of study. Information design is considered the important point in structuring studying materials. It illustrates data that has an objective and make it easier to understand. In addition, good information design help to capture the students' attention which makes them spend longer time on studying without boredom. The aim of the study is to illustrating different tools and techniques that students can utilize within a classroom to promote successful assimilation of information design. The study examined 700 Saudi participants through Twitter and Facebook I 2021. The results reveal that the use of infographics to illustrate information on a graph, watching documentaries and videos promote better study results. Students intend to utilize Google to gather relevant data and information related to their field. The study contributes to educational experts to design affective, interactive and engagement methods in learning. The study provided large data to understand the approached that student prefer and intend to use during their study as well as the reasons behind that.